MUSCULOSKELETAL DISORDERS RELATED TO JANITORIAL SERVICE (Fiep Bulletin - online, 2012)
This study presents an ergonomic risk assessment activities undertaken by ten workers who operate in the cleaning of the Federal Technological University of Paraná, in Curitiba. Therefore, for data collection was a questionnaire Nordic as an interview, in order to identify the existence of work-related musculoskeletal disorders, reported by officials in the last 12 months preceding and the seven days preceding the survey. With the questionnaire, it is noted that the cleaning professionals indicated that the pains occur in more than one body region. The results indicated that the routine work of the employees, which begins without the muscle preparation, it is maintained until the end of the day, causing discomfort and muscle pain often during their work activities. This is due to the fact that the work done has the characteristic of requiring workers crouched positions and repetitive movements in a similar task. It is noteworthy that the employees complained that there is no monitoring activities carried out and there is no instruction as to the possible execution of gymnastics. Thus, it is concluded that the main causes of occurrences of pain coming from work are related to poor posture and lack of education regarding the proper execution of tasks, reasons that can cause serious health problems especially in the spine and joints.
Keywords: Musculoskeletal Disorders; Janitorial Service; Ergonomics.